2021
DOI: 10.1101/2021.12.02.21266523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-method investigation of factors influencing amyloid onset and impairment in three cohorts

Abstract: Alzheimer’s disease biomarkers are becoming increasingly important for characterizing the longitudinal course of disease, predicting the timing of clinical and cognitive symptoms, and for recruitment and treatment monitoring in clinical trials. In this work, we develop and evaluate three methods for modeling the longitudinal course of amyloid accumulation in three cohorts using amyloid PET imaging. We then use these novel approaches to investigate factors that influence the timing of amyloid onset and the timi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…32 Estimated age of amyloid onset (EAOA) was obtained from observed global Pib DVR using a combination of group-based trajectory modeling and Bayes' theorem 33 using either the most recent PET scan (for those who were PiB-) or the scan closest to the PiB+ threshold. Amyloid duration was then estimated as age at plasma sample minus EAOA and the corresponding estimated PiB DVR (GBTM-DVR) was calculated via linear transformation as described in Betthauser et al 34 Centiloids were estimated from these DVRs according to the following equation: 𝐶𝐶𝐿𝐿 = 148.33 × 𝐷𝐷𝐷𝐷𝑅𝑅 − 154.96.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…32 Estimated age of amyloid onset (EAOA) was obtained from observed global Pib DVR using a combination of group-based trajectory modeling and Bayes' theorem 33 using either the most recent PET scan (for those who were PiB-) or the scan closest to the PiB+ threshold. Amyloid duration was then estimated as age at plasma sample minus EAOA and the corresponding estimated PiB DVR (GBTM-DVR) was calculated via linear transformation as described in Betthauser et al 34 Centiloids were estimated from these DVRs according to the following equation: 𝐶𝐶𝐿𝐿 = 148.33 × 𝐷𝐷𝐷𝐷𝑅𝑅 − 154.96.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Mean cortical PiB (cerebellar gray matter reference region) distribution volume ratios were estimated using the Logan method. A global PiB distribution volume ratio greater than 1.19, which corresponds to a centiloid estimate of 22, 8,28 was used to define Aβpositive status 3,27 in the WRAP study.…”
Section: Biomarkersmentioning
confidence: 99%
“…7 However, there is variability in the rates of cognitive decline in preclinical AD. 2,3,[8][9][10][11] Inclusion of individuals with low risk of decline reduces clinical trial power. 4 Successful trials of preclinical AD would benefit from methods to enrich for individuals likely to experience cognitive decline.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another item-level analysis of the MMSE-37 in a Spanish speaking population found that language items were among the best at discriminating between groups with dementia and healthy controls ( Prieto et al, 2012 ). Although we did not examine people with dementia, dementia severity, or progression of AD, it is possible that proper name recall is an ability that is particularly vulnerable to early amyloid pathology; future studies can evaluate item sensitivity to estimated age of onset or projected rate of amyloid accumulation using methods developed by our group ( Koscik et al, 2020 ; Betthauser et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%